Single Center Experience: Enhancing Bacterial Identification Skills in Undergraduate Programs Through the Development of a Web-Based Laboratory Activity - Oktafiani, Devi; Makkiyah, Feda Anisah (Journal of Religion and Public Health, 2021)
asi, perencanaan, pengembangan bentuk produk awal, revisi produk utama, pengujian lapangan utama, revisi produk operasional, pengujian lapangan operasional, dan pengujian produk akhir. Hasil validasi kedua media di atas, kemudian dijumlahkan dan menghasilkan nilai persentase rata-rata 80,38% dengan kategori layak. Dengan demikian media pembelajaran berbasis web ini ditinjau dari aspek kelayakan media pembelajaran oleh para ahli dinyatakan layak digunakan dalam kegiatan pembelajaran. Media pembelajaran berbasis web ini dari aspek kajian kelayakan isi/materi pembelajaran oleh para ahli dinyatakan sangat layak digunakan dalam kegiatan pembelajaran (87,74%). Media pembelajaran berbasis web untuk identifikasi bakteri pada kegiatan laboratorium mikrobiologi terbukti inovatif dan mampu mendukung kegiatan pembelajaran.Kata kunci: Identifikasi bakteri, media pembelajaran, mikrobiologi, berbasis webAbstractMicrobiology is considered to be a difficult subject to learn due to the dense content and frequent use of difficult-to-understand Latin terms in sentences. Developing the web-based modul of this subject will stimulate the student and be more innovative. The research aims to (1) develop web-based learning media for microbiology laboratory activity, and (2) determine the feasibility of the media for learning. This study employed Research and Development (R&D) design and is an adaptation of Borg and Gall's model. This process consists of ten steps: research and information gathering, planning, developing preliminary product form, main product revision, main field testing, operational product revision, operational field testing, and final product testing. The two media validation results above, then summed up and produced an average percentage value of 80.38% with a decent category. Thus, this web-based learning media from the aspect of studying the feasibility of learning media by experts is declared worthy of use in learning activities. This web-based learning media from the aspect of studying the feasibility of the content / learning materials by experts is declared very suitable for use in learning activities (87.74%). Web-based learning media for identification of bacteria in microbiology laboratory activities has been shown to be innovative and capable of supporting learning activities.Keywords: Bacterial identification, learning media, microbiology, web-based